UPAYA ORANGTUA DALAM MEMBIMBING PELAKSANAAN IBADAH SALAT REMAJA PENGGUNA MEDIA SOSIAL DI DESA PARGARUTAN DOLOK ANGKOLA TIMUR - Desi Indriani; Agus Salim Lubis; Maslina Daulay (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2018)
Parents play an important role in instructing and advising adolescents in performing prayers but there are still many teenagers who do not do fardu prayer. From that the researcher wanted to know about the parents' efforts and the obstacles they faced in guiding the implementation of adolescent prayer for social media users in Pargarutan Dolok, East Angkola District. This research method with a descriptive approach in the form of qualitative research that seeks to describe according to phenomena, events and social activities. Data collection through observation and interviews in Pargarutan Dolok, Angkola Timur District, South Tapanuli Regency. The results of the study showed that parents in guiding the implementation of prayer by adolescents who are social media users by giving advice to adolescents to carry out fardu prayers then told adolescents to perform fardu prayers. The obstacles faced by parents in guiding the implementation of adolescent prayer services for social media users are the lack of religious awareness in adolescents, economic and occupational factors, knowledge factors and various kinds of television media and mobile phones